2003
DOI: 10.3989/scimar.2003.67n191
|View full text |Cite
|
Sign up to set email alerts
|

Population study of the fan shell <i>Pinna nobilis</i> L. in Malo and Veliko Jezero of the Mljet National Park (Adriatic Sea)

Abstract: SUMMARY: Although previous studies have noted the presence of the bivalve Pinna nobilis Linnaeus, 1758 in Mljet National Park, there is a lack of basic knowledge of this endangered species. The present study was initiated as part of a long-term investigation of P. nobilis density and growth with the aim of gaining a better understanding of this species' population dynamics, as well as evaluating the efficiency of protection measures of P. nobilis in Mljet National Park. Density, population structure, growth of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 7 publications
3
60
1
Order By: Relevance
“…m −2 (GalinouMitsoudi et al 2006), comparing to the highest density (0.020-0.200 ind. m −2 ) of a studied Mediterranean "recovered" population in the East Adriatic Sea (Šiletić & Peharda 2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…m −2 (GalinouMitsoudi et al 2006), comparing to the highest density (0.020-0.200 ind. m −2 ) of a studied Mediterranean "recovered" population in the East Adriatic Sea (Šiletić & Peharda 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Although there are several publications referring to population studies of P. nobilis (Richardson et al 1999;Šiletić & Peharda 2003;Katsanevakis 2005;GalinouMitsoudi et al 2006;Garcia-March et al 2007), only a single study deals with a partial COI mtDNA sequence in the Pteriomorphia subclass in which P. nobilis belongs (Matsumoto 2003), but it does not include P. nobilis. There is neither nuclear nor mtDNA sequence, as well as no genetic analysis of the species published.…”
Section: Introductionmentioning
confidence: 99%
“…At present, despite decades of combined legal species and habitat protection, common abundances of P. nobilis are less than 1 individual per 100 m -2 (Guallart and Templado 2012), although aggregations of more than 20 individuals per 100 m -2 have been observed in some areas where the species is still abundant (e.g. Siletic and Peharda 2003, Rabaoui et al 2008, Addis et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Possibly for this reason, most studies indicating high P. nobilis densities have only been carried out in areas smaller than 10000 m -2 and the total population reported is usually much lower than 1000 individuals (e.g. Galinou-Mitsoudi et al 2006, Garcia-March and Kersting 2006, García-March et al 2007a, Siletic and Peharda 2003, Addis et al 2009, Zakhama-Sraieb et al 2011). More exceptionally, some studies have explored areas larger than 100000 m -2 and reported populations of thousands of individuals, in addition to very high local densities in discrete areas (Katsanevakis 2006, Katsanevakis andThessalou-Legaki 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Adults were also well represented; in fact large live and dead individuals (>80 cm Ht) were found, although with lower frequency values than small individuals. these large specimens are more than 20 years old (García-March et al,2007a;siletic and Peharda, 2003), and are of particular importance in the spawning and recruitment processes because they represent the source of new individuals.…”
Section: Epibiosismentioning
confidence: 99%